Stress-whitening-resistant, high-rigidity and high-toughness regenerated PP / PE (polypropylene / polyethylene) composite material for vehicles and preparation method thereof

By using new PP materials and recycled PP/HDPE materials in automotive parts, combined with talc powder, POE and compatibilizers, the problems of insufficient strength and whitening in recycled PP and PE materials in automotive parts are solved, and the high rigidity, high toughness and stress whitening resistance of the material are improved, and the recycling and utilization of waste materials is promoted.

CN119798846APending Publication Date: 2025-04-11SHANGHAI PRET COMPOSITES +3
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411975513.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

When used in automotive parts, recycled PP and recycled PE materials are prone to problems such as insufficient strength, cracking and white surface, and their mechanical properties and physical and chemical properties are lower than those of the raw materials.

Method used

The composite material formula consists of new PP materials, new PP materials, laundry bucket recycled PP materials, hollow product recycled HDPE, talc powder masterbatch, POE, compatibility agent, nucleating agent and processing additive are used to improve the compatibility and interface stress of the material and improve the stress resistance of the material.

Benefits of technology

The recycling of waste PP and HDPE materials has been achieved, the stress whitening resistance, rigidity and toughness of composite materials have been improved, and the high standards of automotive parts have been met.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_3
    Figure SMS_3
  • Figure SMS_4
    Figure SMS_4
Patent Text Reader

Abstract

The invention discloses a stress-whitening-resistant, high-rigidity and high-toughness regenerated PP / PE composite material for vehicles. The composite material is prepared from the following components in parts by weight: 25-45 parts of a stress-whitening-resistant brand-new PP material, 10-20 parts of a brand-new PP material, 17-23 parts of a washing drum regenerated PP material, 4-8 parts of hollow product regenerated HDPE, 21-25 parts of talcum powder master batch, 2-5 parts of POE, 1.5-2.5 parts of a compatilizer, 0.1-0.3 part of a nucleating agent, 0.5-1 part of a processing aid and 1 part of color master batch. Compared with a common brand-new PP material, the stress whitening resistant brand-new PP material has the advantages that molecular chains are shorter, micropores or defects generated by molecular chain activity under the stress effect are fewer, and whitening can be relieved; in addition, the relative molecular mass of the rubber phase is lower, rubber particles tend to be stretched and oriented in the melt flowing direction, and the anti-whitening effect is better.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of polymer materials, and specifically relates to a stress-whitening-resistant, high-rigidity and high-toughness automotive recycled PP / PE composite material and a preparation method thereof Background Art

[0002] Recycled polypropylene (PP) refers to the recycled material of PP plastic. Recycling also means recycling. It is the general name for the secondary thermoplastic treatment of new materials. The recycling sources involve the fields of home appliances, daily necessities, industry, transportation, marine garbage, etc. The recycled products include washing machine barrels, turnover boxes, ton bags, car dismantling, fishing nets and fishing gear, etc. PP new material is a thermoplastic synthetic resin with excellent comprehensive performance. It is a colorless, translucent thermoplastic low-density material with excellent mechanical properties, chemical resistance, electrical insulation, heat resistance and easy processing performance. However, when PP is recycled, some of its molecular chains have been broken. Therefore, the recycled PP material has the disadvantages of reduced mechanical properties and poor stress whitening resistance compared to the new material. If the recycled PP material is further applied to automotive parts, the parts are prone to problems such as insufficient strength, cracking, and whitening of the surface.

[0003] The recycling sources of recycled polyethylene (PE) involve the agricultural field, daily necessities, etc. The recycled products include agricultural films, barrels, pots, pallets, pipes, etc. PE new material is a thermoplastic synthetic resin that is odorless, non-toxic, and feels like wax. It has excellent low temperature resistance, chemical stability, and aging resistance. It also has a certain improvement effect on stress whitening. However, the mechanical properties and physical and chemical properties of recycled PE materials are reduced to varying degrees compared with virgin materials.

[0004] However, discarded PP and PE products are not biodegradable materials. Discarded materials can exist in the natural environment for a long time, causing "white pollution". We must continue to work towards the recycling of discarded plastics. However, there are still technical problems that need to be solved in the recycling of recycled PP and recycled PE: some of the recycled PP and PE materials have undergone thermal oxidation aging degradation, the molecular chains have been broken, the basic mechanical properties and physical and chemical properties have been reduced to varying degrees, and the problem of stress whitening will become more obvious. Now, major automobile OEMs are paying more and more attention to the stress whitening problem caused by the injection molding and assembly process of automobile parts, and have raised the standard requirements. Summary of the invention

[0005] In order to overcome the deficiencies of the above-mentioned prior art, the purpose of the present invention is to provide a stress-whitening-resistant, high-rigidity and high-toughness automotive recycled PP / PE composite material, thereby realizing the recycling of waste PP products and waste HDPE products.

[0006] To achieve its purpose, the technical solution adopted by the present invention is:

[0007] A stress-whitening-resistant, high-rigidity and high-toughness recycled PP / PE composite material for automobiles comprises the following components in parts by weight: 25-45 parts of new PP material that is stress-whitening-resistant, 10-20 parts of new PP material, 17-23 parts of recycled PP material for washing tubs, 4-8 parts of recycled HDPE for hollow products, 21-25 parts of talc masterbatch, 2-5 parts of POE, 1.5-2.5 parts of a compatibilizer, 0.1-0.3 parts of a nucleating agent, 0.5-1 parts of a processing aid, and 1 part of a masterbatch. Compared with ordinary new PP material, the stress-whitening-resistant new PP material has a shorter molecular chain, and fewer micropores or defects generated by the activity of the molecular chain when subjected to force, which is conducive to reducing whitening. In addition, the relative molecular mass of the rubber phase is lower, and the rubber particles tend to be stretched and oriented along the melt flow direction, so the anti-whitening effect is better.

[0008] From the perspective of crystal type, the stress whitening problem of materials is analyzed. Compared with α crystal (lamellar interlocking structure), β crystal is easier to slip and plastically deform, so it has better resistance to stress whitening. Stretching and other stress concentrations can easily cause the material crystal type β crystal to α crystal. As the α crystal content gradually increases, the stress whitening phenomenon becomes more obvious. The good rigidity of PP and the excellent low-temperature impact resistance of HDPE are combined together, and their respective advantages are synergistically exerted. Combined with mineral fillers, toughening agents, compatibilizers, nucleating agents, etc., a composite material for automobiles with high rigidity and high toughness is formed. In addition, HDPE can form a core-shell structure with the dispersed phase of PP material. HDPE has a higher degree of crystallinity and greater shrinkage, which leads to a greater shrinkage and smaller size of this core-shell structure. It has better and more uniform dispersion in the entire composite material, and also plays a certain role in improving the material's resistance to stress whitening.

[0009] However, the basic mechanical properties, high temperature resistance and chemical resistance of the washing machine tub PP recycled material and the hollow product HDPE recycled material are reduced to varying degrees compared with the new material. The compatibility between the two and talcum powder is also poor, and the interfacial stress is strong, which makes it easier to produce defects such as microcracks and micropores, forming microcrack aggregation areas. From a macroscopic point of view, the refractive index of the product surface changes, which is the stress whitening phenomenon. During the experiment, the inventor tried various compatibilizers to improve the compatibility between the new PP resistant to stress whitening, the washing tub PP recycled material, the hollow product HDPE recycled material and talcum powder, and reduce the interfacial stress between the components. During the experiment, it was found that not every compatibilizer can play a good role. After a large number of experiments, it was found that when polypropylene grafted maleic anhydride copolymer (PP-g-MAH) and polyethylene grafted maleic anhydride copolymer (PE-g-MAH) are used as compatibilizers, the compatibility between new PP materials with stress whitening resistance, laundry tub PP recycled materials, hollow product HDPE recycled materials and talcum powder can be better reduced. The interfacial stress between the components is reduced, which greatly improves the mechanical properties and stress whitening resistance of the composite materials.

[0010] The addition of talcum powder will also affect the rigidity and stress whitening resistance of the composite material. Mineral fillers can increase the rigidity and strength of the matrix material, inhibit the plastic deformation of the matrix, and improve whitening. After trial and error, it was found that the use of talcum powder with a smaller particle size and a higher mesh number can greatly improve the stress whitening resistance and mechanical properties of the composite material. In the case of the same filler, the higher the mesh number, the stronger the heterogeneous nucleation effect on the crystalline matrix material, promoting the perfection of the lattice and improving whitening.

[0011] The addition of POE can improve the toughness and low-temperature impact resistance of the composite material, but it has no effect on the material's stress whitening resistance or even worse effect. In terms of the selection of POE, the inventors tend to choose elastomers with shorter molecular chains and better compatibility with the matrix material. The better the dispersibility in the matrix material, the more obvious the stress whitening improvement effect.

[0012] Another factor that affects the mechanical properties and stress whitening resistance of composite materials is the addition of nucleating agents. After the nucleating agent is added to the PP matrix, it can act as a crystal embryo during the cooling and recrystallization process, transforming the original homogeneous nucleation into heterogeneous nucleation. Due to the large number of crystal nuclei, the overall material crystallization rate is faster, the crystals are more refined, and the crystal size is much smaller than the spherulites without the addition of nucleating agents. Compared with the original spherulites with large defects, the addition of nucleating agents can improve the stress whitening resistance and comprehensive mechanical properties of PP to a certain extent.

[0013] In the present invention, preferably, the melt index of the PP new material at 230°C and a load of 2.16kg is 25-65g / 10min; more preferably, the melt index of the PP new material at 230°C and a load of 2.16kg is 45-60g / 10min.

[0014] In the present invention, preferably, the melt index of the stress-whitening resistant PP new material at 230°C and a load of 2.16kg is 30-50g / 10min; more preferably, the melt index of the PP new material at 230°C and a load of 2.16kg is 35-45g / 10min.

[0015] In the present invention, the washing machine barrel PP recycled material is recycled material from waste washing machine inner drum. Preferably, the melting index of the washing machine barrel PP recycled material at 230°C and a load of 2.16kg is 30-50g / 10min; more preferably, the melting index of the washing machine barrel PP recycled material at 230°C and a load of 2.16kg is 35-45g / 10min.

[0016] In the present invention, the hollow product HDPE recycled material can be waste recycled materials such as domestic or industrial barrels, bottles, and pots. Preferably, the melting index of the hollow product HPDE recycled material at 190°C and a load of 5kg is 3-10g / 10min; more preferably, the melting index of the hollow product HPDE recycled material at 190°C and a load of 5kg is 5-8g / 10min.

[0017] In the present invention, the melt index and grafting rate of PE-g-MAH and PP-g-MAH grafts have a great influence on the compatibility between PP new material, washing machine barrel PP recycled material, film HDPE recycled material and talcum powder. If the melt index of PE-g-MAH and PP-g-MAH grafts and PP new material, washing machine barrel PP recycled material, and hollow product HDPE recycled material is greatly different, it will not only affect the compatibility between the compatibilizer and the matrix material, but also greatly affect the processing fluidity of the composite material and the appearance of the product; if the grafting rate of the compatibilizer is too low or too high, it will also affect the compatibility between the stress-whitening PP new material, washing machine barrel PP recycled material, hollow product HDPE recycled material and talcum powder, thereby reducing the stress-whitening resistance and mechanical properties of the composite material.

[0018] In order to maintain high rigidity, high toughness and stress whitening resistance of automotive composite materials, preferably, the grafting rate of the PP-g-MAH graft is 20%-35%, and the melt index at 190°C and a load of 2.16kg is 25-35g / min; more preferably, the grafting rate of the PP-g-MAH graft is 25%-30%, and the melt index at 190°C and a load of 2.16kg is 28-33g / min.

[0019] In order to maintain the high rigidity, high toughness and stress whitening resistance of automotive composite materials, preferably, the grafting rate of the PE-g-MAH graft is 20%-30%, and the melt index at 190°C and a load of 2.16kg is 3-7g / min; more preferably, the grafting rate of the PE-g-MAH graft is 22%-28%, and the melt index at 190°C and a load of 2.16kg is 3.5-5.5g / min.

[0020] In the present invention, the added talc powder with smaller particle size and higher mesh number is helpful to improve the rigidity, tensile strength, elastic modulus, flexural strength, flexural modulus, heat deformation temperature and stress whitening resistance of the composite material for automobiles.

[0021] In the present invention, the added POE with shorter molecular chain and better compatibility with the PP matrix helps to improve the toughness, impact strength, notched impact strength, elongation at break, etc. of the automotive composite material, and largely avoids the influence on the material's stress whitening resistance.

[0022] The processing aid is one or more of a nucleating agent, an antioxidant, a plasticizer, a lubricant, and a light stabilizer.

[0023] The nucleating agent is selected from NX 8000, One or more of Z100, LPN-9086.

[0024] The antioxidant is selected from one or more of 1010, 1076, 245, 168, DSTP, 1098, and A203.

[0025] The plasticizer is selected from one or more of alkylbenzene sulfonate, epoxidized oleic acid glyceride, dioctyl phthalate, hydrogenated ricinoleic acid glyceride and polyethylene wax.

[0026] The selected lubricant is selected from one or more of zinc stearate, PP wax and oleic acid amide.

[0027] The selected light stabilizer is one or more selected from 770, 622, 944, UV-3853PP5, and TINUVIN 791.

[0028] The specific steps of the preparation method of the above-mentioned stress-whitening-resistant, high-rigidity and high-toughness automotive recycled PP / PE composite material are as follows:

[0029] S1: PP washing machine barrel recycled material and HDPE hollow product recycled material are prepared by screening, crushing, washing, drying, color screening, electrostatic selection, homogenization batch mixing, extrusion granulation, and secondary homogenization batch mixing respectively;

[0030] S2: Weigh the raw materials of each component according to the formula, mix them evenly in a high-mix mixer, and then melt-blend, extrude, cool and granulate them in a twin-screw extruder.

[0031] Preferably, the processing temperature in step S1 is: 120℃-230℃; the speed of the high-mix mixer in step S2 is 300-15000r / min, and the mixing time is 9-10min; the speed of the twin-screw extruder in step S2 is 450-750r / min, the conveying section temperature is 75℃-120℃, the melting section temperature is 140℃-180℃, the homogenization temperature section is 180℃-230℃, the vacuum degree is -0.08MPa--0.10MPa, and the screw aspect ratio is greater than 45:1.

[0032] Compared with the prior art, the present invention has the following beneficial effects:

[0033] The mechanism of improving the material's stress whitening resistance is different from the traditional method of simply increasing the color powder concentration of the material, and plays a simple visual covering role. The present invention improves the material's stress whitening resistance while ensuring the mechanical properties of the composite material by adding a new PP material that resists stress whitening. At the same time, by adding talcum powder mineral filler, toughening agent POE, nucleating agent and compatibilizer, new PP, recycled PP and recycled HDPE are synergistically enhanced and toughened, and the obtained automotive composite material has both good rigidity and stress whitening resistance, and good toughness and impact resistance. The stress whitening resistant, high rigidity and high toughness automotive recycled PP / PE composite material provided by the present invention also realizes the recycling of discarded PP washing machine barrel materials and discarded HDPE hollow product materials. DETAILED DESCRIPTION

[0034] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the following is further described in conjunction with specific examples. Obviously, the following examples are only typical descriptions of the present invention, not all embodiments. It should be understood that the embodiments of the present invention are only used to illustrate the technical effects of the present invention, and are not used to limit the scope of protection of the present invention. In the following embodiments, the melt index of PP brand new material at 230°C and a load of 2.16kg is 50g / min; the melt index of stress-whitening PP brand new material at 230°C and a load of 2.16kg is 40g / min; the melt index of PP washing machine barrel recycled material at 230°C and a load of 2.16kg is 35g / min; the melt index of HDPE hollow product recycled material at 190°C and a load of 5kg is 5.5g / min. The raw materials of the embodiments and comparative examples can be purchased commercially, and the same one is used for parallel experiments. The test methods used are conventional methods unless otherwise specified.

[0035] The following is a description of some raw material information, but it is not limited to these materials:

[0036] PP new material, M50RH, from Sinopec Zhenhai Refining and Chemical Company;

[0037] Stress-whitening PP new material, M30-L, Sinopec Hainan Refining and Chemical Co., Ltd.;

[0038] Talc masterbatch, talc content 85%, particle size 5000 mesh, Dongguan Sanlong New Material Technology Co., Ltd.;

[0039] POE, DF610, Mitsui, Japan;

[0040] PP-g-MAH, SK Chemical, South Korea;

[0041] PE-g-MAH, SK Chemical, South Korea;

[0042] Antioxidant, antioxidant 1010, commercially available;

[0043] Plasticizer, dioctyl phthalate, commercially available;

[0044] Lubricant, PP wax, commercially available.

[0045] Masterbatch, light grey, color powder content 80%, homemade.

[0046] 1. Examples 1-6

[0047] (1) Screening, crushing, cleaning, drying, color screening, electrostatic selection, homogenization batch mixing, extrusion granulation, and secondary homogenization batch mixing of waste PP washing machine barrels and waste HDPE hollow products to obtain PP washing machine barrel recycled materials and HDPE hollow product recycled materials;

[0048] (2) Weigh PP new material, PP recycled material, HDPE recycled material, PP-g-MAH, PE-g-MAH, talcum powder masterbatch, POE and add them into a mixer and mix at low speed for 3-6 minutes, then add nucleating agent, antioxidant, light stabilizer, lubricant, plasticizer and the like and mix for 7 minutes; put the mixed materials into a high-speed mixer and mix for 9-10 minutes, then melt blend, extrude, cool and pelletize through a twin-screw extruder to obtain the stress-whitening resistant, high-rigidity and high-toughness automotive PP / PE composite material. The temperature of the twin-screw extruder is set as follows: the conveying section temperature is 75℃-120℃, the melting section temperature is 140℃-180℃, the homogenization temperature section is 180℃-230℃, the vacuum degree is -0.08MPa--0.10MPa, and the screw aspect ratio is greater than 45:1.

[0049] Comparative Examples 1-3 provide a modified recycled PP / PE composite material, the weight formula of which is shown in Table 1, and the preparation method refers to the preparation method of Example 3.

[0050] Table 1

[0051]

[0052] Note: “-” in the table means that the component is not added.

[0053] Comparative Examples 1-3

[0054] The preparation method is the same as that of Examples 1-6, the main differences being that no recycled material is added in Control Example 1, no nucleating agent is added in Control Example 2, and no compatibilizer is added in Control Example 3.

[0055] 2. Performance Test

[0056] The recycled PP composite materials prepared in Examples 1-6 and Comparative Examples 1-3 were subjected to performance tests, and the test methods were as follows:

[0057] (1) Tensile strength is tested according to ISO527-2:2012 standard;

[0058] (2) Flexural modulus is tested according to ISO178:2019 standard;

[0059] (3) Flexural modulus is tested according to ISO178:2019 standard;

[0060] (4) Simply supported beam notched impact strength is tested according to ISO179-1:2010 standard

[0061] (5) The whitening state is tested according to the SAIC Passenger Car SMTC 5 400 249 standard.

[0062] The test results are shown in Table 2.

[0063] Table 2

[0064]

[0065] As can be seen from the results of Table 2, Examples 1-4, as the content of stress-whitening PP new material added increases, the whitening of the material becomes less and less obvious, until the material does not whiten when the content is added to 30 parts or more, and the mechanical properties are slightly reduced. It shows that the PP raw materials with shorter molecular chains and lower relative molecular mass of the rubber phase have fewer micropores or defects generated by the molecular chain activity when subjected to force, and the rubber particles tend to stretch and orient along the melt flow direction, and the anti-whitening effect is better. It can be seen from Examples 3 and 6 that the mechanical properties and whitening state of Example 3 with a higher mesh number of talcum powder added are significantly better than those of Example 6 with a lower mesh number of talcum powder added. It shows that the higher the mesh number and smaller the particle size of the added talcum powder, the better the dispersibility in the PP matrix, and the better the overall performance of the material. It can be seen from Example 2 and Comparative Example 1 that the addition of PP and PE recycled materials has a certain effect on the mechanical properties and stress-whitening resistance of the composite material. It shows that the local breakage of the molecular chain of the recycled material itself is more likely to produce defects such as microcracks and micropores, affecting the overall performance of the composite material. It can be seen from Example 3 and Comparative Example 2 that the addition of nucleating agents improves the rigidity and whitening state of the material, indicating that the nucleating agent will make the overall material crystallize faster, the crystals more refined, and the crystal size is much smaller than the spherulites without the addition of nucleating agents. Compared with the original spherulites with large defects, the addition of nucleating agents can improve the stress whitening performance and comprehensive mechanical properties of PP to a certain extent. It can be seen from Example 3 and Comparative Example 3 that the addition of compatibilizers PP-g-MAH and PE-g-MAH improves the rigidity and whitening state of the material, indicating that the compatibilizer can better reduce the compatibility between new PP materials, laundry tub PP recycled materials, hollow product HDPE recycled materials and talcum powder, reduce the interfacial stress between the components, and improve the mechanical properties and stress whitening resistance of the composite material.

[0066] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A stress-whitening-resistant, high-rigidity and high-toughness recycled PP / PE composite material for automobiles, characterized in that: The invention comprises the following components in parts by weight: 25-45 parts of new stress-whitening PP material, 10-20 parts of new PP material, 17-23 parts of recycled PP material for washing tub, 4-8 parts of recycled HDPE for hollow products, 21-25 parts of talc masterbatch, 2-5 parts of POE, 1.5-2.5 parts of compatibilizer, 0.1-0.3 parts of nucleating agent, 0.5-1 parts of processing aid and 1 part of masterbatch.

2. The stress-whitening-resistant, high-rigidity and high-toughness recycled PP / PE composite material for automobiles according to claim 1, characterized in that: The new PP has a melt index of 45-60 g / 10 min at 230° C. and a load of 2.16 kg.

3. The stress-whitening-resistant, high-rigidity and high-toughness recycled PP / PE composite material for automobiles according to claim 1, characterized in that: The stress-whitening resistant new PP has a melt index of 35-45 g / 10 min at 230° C. and a load of 2.16 kg.

4. The stress-whitening-resistant, high-rigidity and high-toughness recycled PP / PE composite material for automobiles according to claim 1, characterized in that: The melting index of the recycled PP for the washing machine barrel is 35-45 g / 10 min at 230° C. and a load of 2.16 kg.

5. The stress-whitening-resistant, high-rigidity and high-toughness recycled PP / PE composite material for automobiles according to claim 1, characterized in that: The melt index of the recycled HDPE for the hollow product is 5-8 g / 10 min at 190° C. and a load of 5 kg.

6. The stress-whitening-resistant, high-rigidity and high-toughness recycled PP / PE composite material for automobiles according to claim 1, characterized in that: The talc powder masterbatch has a talc powder content of 80-90% and a particle size of 4000-6000 meshes.

7. The stress-whitening-resistant, high-rigidity and high-toughness recycled PP / PE composite material for automobiles according to claim 1, characterized in that: The grafting rate of the compatibilizer PP-g-MAH graft is 25%-30%, and the melt index is 28-33g / min at 190°C and a load of 2.16kg; the grafting rate of the compatibilizer PE-g-MAH graft is 22%-28%, and the melt index is 3.5-5.5g / min at 190°C and a load of 2.16kg.

8. The stress-whitening-resistant, high-rigidity and high-toughness recycled PP / PE composite material for automobiles according to claim 1, characterized in that: The processing aid is one or more of a nucleating agent, an antioxidant, a plasticizer, a lubricant, and a light stabilizer.

9. The method for preparing the stress-whitening-resistant, high-rigidity and high-toughness recycled PP / PE composite material for automobiles according to any one of claims 1 to 8, characterized in that: The specific steps are as follows: S1: PP washing machine barrel recycled material and HDPE hollow product recycled material are prepared by screening, crushing, washing, drying, color screening, electrostatic selection, homogenization batch mixing, extrusion granulation, and secondary homogenization batch mixing respectively; S2: Weigh the raw materials of each component according to the formula, mix them evenly in a high-mix mixer, and then melt-blend, extrude, cool and granulate them in a twin-screw extruder.

10. The preparation method according to claim 9, characterized in that: The processing temperature in step S1 is: 120°C-230°C; the speed of the high-mix mixer in step S2 is 300-15000r / min, and the mixing time is 9-10min; the speed of the twin-screw extruder in step S2 is 450-750r / min, the conveying section temperature is 75°C-120°C, the melting section temperature is 140°C-180°C, the homogenization temperature section is 180°C-230°C, the vacuum degree is -0.08MPa--0.10MPa, and the screw aspect ratio is greater than 45:1.

Citation Information

Patent Citations

  • Stress-whitening-resisting glass fiber reinforced polypropylene composite and preparation method thereof

    CN102924805A

  • Anti-stress-whitening master batch, anti-stress-whitening halogen-free intumescent flame-retarding polypropylene composite material and preparation methods thereof

    CN108102222A

  • Low-cost anti-whitening polypropylene special material for bags and suitcases and preparation process thereof

    CN112194847A

  • Low-VOC (volatile organic compound) regenerated PP (polypropylene) composite material for rigid-tough balance vehicle and preparation method thereof

    CN117866323A